Evaluasi Kinerja Makro Ekonomi dan Keuangan Daerah (Studi Komperatif: Kota Padang dan Kota Bukittinggi - Pasaribu, Rahmat (Jurnal Ekonomi, 2012)
This research aims to avaluate macro economy and financial performance as a money follow function in regional autonomy implementation by comparative study in Padang and Bukittinggi Munipacility in 2005-2008 fiscal years. The result shows the economy structure of Padang from the economic sector's contribution to GDP is not so much different from Bukittinggi; the purchasing power of Padang and Bukittinggi indicate increasing trend; highest inflation rate in 2008 in Bukittinggi on average goods and services; unemployment rate in Padang and Bukittinggi during the 2007-2008 period experienced significant growth, respectively grew by 10,90% and 7,71%; Padang tas ratio is quite stable average os 0,95% per year, while the tas rate of Bukittinggi is an average of 0,86% er year; while the ratio of local financial performance of Padang and Bukittinggi was good but this result is inversely proportional when compared to 2006 and 2007 respectively by -0,50 and -0,29 (elasticitu minus indicates that the performance of local government is not optimal). Finally, the ability of local financial of Padang and Bukittinggi in 2005-2006 has decreased but increased in 2007.